RECRUITMENT OF LAW FACULTY LECTURERS AND THE IMPLICATIONS OF OUTPUT GRADUATES IN THE MANPOWER SECTOR - Rifka Yudhi; Prastyo, Agung Budi (Progressive Law Review, 2020)
The symmetrical relationship that shapes the quality of graduates cannot be separated from the existence of Human Resources, namely qualified lecturers. A qualified lecturer is produced by quality recruitment and continuous coaching. Because the curriculum is as great as it is, with lecturers who have no motivation or even the ability to interpret texts and contexts, it is certain that they experience difficulties in presenting an optimal learning method and in the end have a significant effect on the output of graduates. The focus of this article is: (1) to understand in depth why the lecturer recruitment process has a strong correlation with the quality of public services; and (2) to know and understand how the quality of law faculty lecturers affects output graduate. This research was conducted with a normative juridical approach, because in this study the assessment was carried out based on legal norms and principles, applicable laws and regulations and other library materials relevant to the research topic. The conclusions obtained, among others, show that: (1) The process of recruiting lecturers to PNS Lecturers, Permanent PNS Lecturers and Permanent PTS Lecturers will affect the quality of public services in the university scope. This is based on several factors, including intention, quality commitment, individual quality, and how the work unit, namely universities and faculties, always carries out intensive coaching for young lecturers who have been recruited in the context of implementing the Tri Darma of Higher Education; (2) The quality of a lecturer is obtained through a long process since his early days as a lecturer which can be achieved through seriousness, focus, and consistency through a continuous coaching process. The qualities possessed by a law faculty lecturer also contribute to shaping the mindset, understanding, and competence of students that have an impact on output graduate. The further impact of the output of this graduate is the extent to which a university graduate can be absorbed in the world of work, be it in Ministries, Institutions, Agencies or Regional Governments, as well as in private agencies.